UJI PBNGARUH MODERASI PADA ANALISIS REGRESI MENGGUNAKAN UJI NILAI SELISIH MUTLAK - Lie Liana (Jurnal Ilmiah Dinamika Teknik, 2009)
Independent variable can correlate indirect and also direct with variables of dependen. This indirec can influence by existence of variable of moderating. variable of moderating this can strengthen or weaken independen variable and variable of dependen. nature of or direction independent variables with variables of dependen earn negative or positive depend onvariable moderating. There are some test to test influence of variable of moderating this, among others test asses absolute difference. Test assess this absolute diffrence represent examination to influence of moderasi by using model asses absolute difference of independen variable. keyword: variable of moderating, test asses absolute difference